Menelusuri Kekerabatan Bahasa Jawa, Madura, dan Bali: Kajian Austronesia dalam Leksikon Sapaan Anggota Keluarga - Sholihah, Idatus (Crises on Languages and Literature, 2026)
This study aims to reveal the similarities in form and meaning of family member terms in Javanese, Madurese, and Balinese as Austronesian languages. This study uses a qualitative descriptive method with a historical-comparative linguistic approach. Data were obtained through a literature study of dictionaries and relevant scientific sources, then analyzed using the principle of regular sound correspondence to identify cognate forms and phonological innovations that occurred. The results show that lexical terms of address such as bapa, adi, and nini have forms and meanings that are consistent with Proto-Austronesian forms. Balinese tends to be the most conservative in retaining proto forms, Javanese shows minor innovations through vowel changes and speech level systems, while Madurese has undergone phonological changes, including the emergence of glottal stops and aspirated consonants. Semantically, all three languages retain the basic meanings that represent core kinship relationships, albeit with their own variations.